Optimasi Efektivitas Operasional Melalui Transformasi Alur Pemesanan Manual Menjadi Terstandarisasi pada Bisnis Franchise F&B - Zian Nur Fadhilah; Muhammad Syihabuddin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The booking process with the food and municipal business (f&b) has an important part to contribute to the direct distribution of goods from the center to the partner. However, in xyz group, booking processes are still carried out by hand through unstructured format whatsapp messages, which leads to nonuniform data, miscommunication, and slow record keeping and distribution processes. This research aims to design standardized reservations forms as more effective course improvements solutions without the need for complex application development. The research method used is a qualitative description with a case study approach. Data collection techniques were made through direct observation during apprenticeship as well as detailed booking channels. In addition, the study adopted the system design approach (prototyping) in composing the proposal reservations system. Research shows that application of standardized booking forms can improve order order order order, improve information accuracy, and reduce the need for clarification by section MCC. The proposed system also facilitated the process of data recapitulation and increased the efficiency of divisional coordination, supporting the distribution operational efficiency of the F&B franchise.